Quality of life of people with disabilities during COVID-19 pandemic - Gałwiaczek, Sandra (Jakość życia osób z niepełnosprawnością podczas pandemii COVID-19, 2021)
The study analyses the quality of life of people with disabilities during the Covid-19 pandemic based on the data collected from the survey. The logit model, linear model, Chi-squared test and significance test for proportions were used. The study found that during the pandemic the main influence on quality of life of disabled people came from variables that deteriorated the respondents’ mental health.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2021, Nr 19 (25), s. 53-65
Keywords: disability; quality of life; pandemic; mental health; niepełnosprawność; jakość życia; pandemia; zdrowie psychiczne; COVID-19